Coupling turbulent natural convection-radiation-conduction in differentially heated cavity with high aspect ratio - Benyahia, Nabil; Aksouh, Mohamed; Mataoui, Amina; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2020)
In this paper, the effect of a several combined heat transfer processes: turbulent natural convection, surface radiation and conduction, are investigated numerically in an air-filled three-dimensional (3D) differentially heated tall cavity. The objectives of this work is to analyse the effect of coupled of different heat exchanges on flow structures of turbulent natural convection, and to distinguish the most realistic thermal boundary conditions of internal walls providing thus more accurate results. The cavity is parallelepiped 1and extended with sides length 0.076 x 2.18 x 0.52 m. A temperature gradient between the lateral walls is subjected of Delta T = 19.9 degrees C., inducing a turbulent flow due to the high Rayleigh number (Ra-H = 2.03 x 10(10)). A three dimensional unsteady numerical simulations are performed by the finite volume method using the Shear Stress Transport (SST k-omega) model and using the P-1 thermal radiation model. The effect of surface thermal radiation on heat transfer and dynamic structure is examined through a different values of internal surface emissivity of epsilon = [0, 0.6] and the air is assumed non-participating medium. Also, different previously works concluded that the heat conduction of passive walls must be considered for more accurate prediction. However, the heat conduction is considered in the likewise direction by imposing a temperature distribution along adiabatic walls. In the present study, the thickness of horizontal walls is specified in order to consider the normal heat conduction as a new approach in physical modelling of an enclosed cavity. The present numerical results are compared to available experimental databases for the same flow configuration. A numerical predictions show that the emissivity of the internal walls influences essentially the flow structures close to the horizontal walls, without any effects on the flow in the core of the cavity. On the other hand, somewhat accurate numerical predictions are obtained with combined different heat transfer along internal walls of differentially heated cavity.
Keywords: CFD; Natural convection; Turbulence; Heat transfer; Surface radiation